(untitled) (Journal of Oriental Studies, 2017)
In this article examined to the сonnection between personal pronoun and possessive pronoun in Turkish languages. We a form that grew short to classify possessive completion my consciousness talks we examine. Sound of н in possessive composition of completions to classify me the general is activity of sound of н on my consciousness personalities.